Growing up and growing apart/growing up and growing closer : a look at the long-term fandoms of Sandy Lam and Kit Chan. - Liew, Hattie Hanming. (2013)
What is fandom? Studies on fan culture in Asia have been occupied with issues of identity and resistance. However, it is unclear what shape fandom takes, or how and why it is sustained. In the kaleidoscopic media environment in Singapore, this study seeks to understand two groups of long-time Mando/Canto-pop fans. Interviews with fans of Hong Kong singer Sandy Lam, and that of Singaporean singer Kit Chan, reveal that the sustenance and evolution of their fandoms take on very different forms and intensities. While both groups declare themselves as huge, long-term fans, Lam’s fandom is affective, yet intellectual; a hybrid of what Shuker (2008) describes as “fans” and “aficionados”. Chan’s fandom, on the other hand, can be described as ambivalent for most part. In understanding the differences, five binary themes are explored. Firstly, “de-centered/centered” takes a look at how fan ecologies’ shape fandom. Secondly, “shame/pride” discusses fans’ perception of their fan identities, and hence their performance of fan practices. This contributes partly to how much the fan integrates fandom into his life, explored in the third theme, “separation/integration”. Their motivation for sustaining their fandom will be investigated in the fourth theme, “nostalgia/renewal”. Finally, the para-social interaction that is instrumental to fan-celebrity relationships is discussed in “desired-reality/perfect-fantasy”. Through these themes, the derivation of pleasure from fandom (or lack thereof) in the context of living in Singapore explains the different experiences. In addition, informed by the general social climate in Singapore and the depoliticized nature of contemporary Mandopop, fandom in either group is unlikely to go beyond personal transformation to be that agent of social or political change seen in other parts of the world.